APPLICATION OF PEDAGOGICAL SITUATIONS IN THE EDUCATIONAL PROCESS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article shows the use of pedagogical, problem situations in the educational process, shows the meaning of the problem, stimulation, gives examples, shows the structure and essence of problem situations.